QbD enabled optimization study of the variable concentration of phospholipid and stabilizer in the development of liposomal pastilles of solid dispersion polymeric composite of antihypertensive drug - Gupta, Ram Dayal; Sharma, Vijay; Aggarwal, Deepti (Journal of Applied Pharmaceutical Research, 2025)
Background: The study aimed to develop and optimize liposomes of the antihypertensive drug Felodipine (FH) using the Quality by Design (QbD) approach with a 3² Central Composite Design (CCD) in Design Expert software, followed by the development of pastilles. Methodology: Liposomes were prepared using the solvent injection method, with soya lecithin and cholesterol as key excipients, and a solid dispersion of FH. The impact of their concentrations on particle size (PS), drug content (DC), entrapment efficiency (EE), and in vitro and ex vivo drug release was analyzed using response surface methodology. The optimized formulation was validated using four batches (optimized batch, VC1, VC2, and VC3), ensuring a minimal percentage error. The liposomal formulation was incorporated into pastilles to enhance patient compliance, and these were evaluated for drug content, dissolution, bioadhesion, and stability. Results and Discussion: The optimized liposomes exhibited desirable properties, including a positive surface charge (PS, 1.41±0.12), a high DC (94.323±1.03), a high EE (69.61±1.13), in vitro drug release (70.73±1.08), and ex vivo drug release (66.88±0.23). The validation batches showed minimal percentage error, confirming the optimization process. The pastilles demonstrated excellent physical stability and bioadhesion, indicating their potential for improved patient compliance. Conclusion: The study showed the effectiveness of the QbD approach in optimizing a liposomal drug delivery system for FH, thereby minimizing the need for extensive trials. The incorporation of liposomes into pastilles provided a patient-friendly dosage form with enhanced bioadhesion and stability, making it a promising alternative for antihypertensive drug delivery.